PERLINDUNGAN HUKUM TERHADAP EKSISTENSI LAYANG -LAYANG TRADISIONAL BALI SEBAGAI PENGUATAN PARIWISATA BUDAYA - Udytama, I Wayan Wahyu Wira (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
The soul of Bali tourism is cultural tourism, where one aspect of culture that became a tourist attraction in Bali is a traditional Balinese Kite. This research aims to find out how the protection of traditional Balinese kites as strengthening the Bali culture associated with cultural tourism.The author takes the method in writing in the form of the empirical method, which method to use facts as a major analysis by linking the law who live in the community and using descriptive analytical approach.The results of this paper is the existence of the protection of traditional Balinese kites only to the extent of organizing events conducted between local government and traditional Balinese kites Sekehe, Pakraman own sheltered by giving space to young people to work in traditional Balinese kites.